Anarchism : a very short introduction - Prichard, Alex (Oxford : Oxford University Press, 2022)
This short book provides a new point of departure for our understanding of anarchism. It questions standard understandings of anarchy and anarchism as an ideology of chaos and disorder, and sheds new light on anarchism as a lived set of prefigurative practices, with a rich historical legacy. The book explores anarchist approaches to public health provision, education, work, law and order, and world politics, including topics of war and violence, federalism, and climate change. By locating the emergence of anarchist ideas in a global history of colonialism and imperialism, it links anarchism into struggles for freedom across the world, and argues that anarchism still holds value for thinking about new models of freedom and democracy today.
Acknowledgements -- List of illustrations -- 1 The origins of anarchism -- 2 The globalization of anarchism -- 3 Anarchism today -- 4 Anarchism and the provision of public goods: health and policing -- 5 Anarchism and the provision of public goods: work and education -- 6 Anarchism and world politics -- References -- Further reading -- Index.
Previously issued in print 2022.
Includes bibliographical references and index.
Also available in Print and PDF edition.
Description based on Publisher website; title from home page (viewed on July 07, 2022).
Keywords: Anarchism; Anarchism -- History; Anarchists; Electronic books